Amor ao próximo em vez de ódio, vingança e rancor: um estudo exegético de Lv 19,17-18 - Santos, Maria Cristiane dos (2020)
In this Master's Dissertation there is an exegetical study of Lv 19,17-18. It is a small set of six imperative laws, receiving, in addition, the formula of self-presentation of the LORD, God of Israel. The text was originally composed in Hebrew and is part of the literary work of the Pentateuch, that is, of the Torah. Two Chapters make up the Dissertation. In the first one, the linguistic-literary and / or poetic configuration of the set of legal formulations in Lv 19,17-18 is studied. Commonly, then, only the poeticity of biblical narratives is recognized. They are epic poetry. Similarly, chants, sets of proverbs and / or prophetic speeches reveal literary beauty as lyrical poetry. With this, however, the question arises regarding legal traditions, which occupy almost half of the Pentateuch. That is, when classifying the Bible as literature, it is also necessary to investigate the sets of laws in view of their poetic configurations. Therefore, in this Dissertation, such research occurs with the literary unit of Lv 19,17-18. After segmenting the text, on the basis of an exact analysis of the composition of each sentence, we look for the stylistic elements that were used at the time of the poetic configuration of the set of laws in question. In this sense, it will be possible to observe several types of parallelisms, a concentric structure and the multiple placement of certain elements according to numbers, which apparently have symbolic connotations. With this, the technical concept of “legal poetry” is proposed, when it aims at the literary genre of laws. In the second Chapter, the Dissertation aims at historical-theological studies in relation to the legal formulations in Lv 19,17-18. What is being considered, when the Israeli legislator forbids to hate the brother, put sin on him, take revenge or be resentful towards the children of the people? And what is the proposal, when the legislator prescribes the reprimand of the compatriot and, par excellence, the love for one's partner or neighbor? In fact, who is this “next”? In view of this, the fifty-two presences of that word in the work of the Pentateuch will be controlled, the most immediate literary-theological context of Lv 19,18c. Is the “neighbor”, par excellence and / or exclusively, the one who belongs to the same ethnicity, the same clan and / or the same family, or does the concept of “neighbor” need to be applied more broadly?